Hemp Microbiome Composition and Function Under Developing Pest Management Solutions - Allison M. Rietman; Lucía Amani; Connor N. Morozumi; Nicole A. Gauthier; Natalie Christian (Phytobiomes Journal)
Conventional pesticides used in cropping systems prevent damage caused by pathogens and pests but may also have unintended consequences for nontarget organisms associated with plants. For example, fungicide application may affect microbes such as fungal endophytes that potentially confer protective benefits to the host, such as pathogen or pest resistance. Here, we investigated how fungicide application and pathogen inoculation altered the communities of pathogenic and nontarget endophytic leaf microbes in hemp (Cannabis sativa L.). We found that fungicide application and inoculation with fungal pathogens affected hemp-associated microbial communities. Fungicide application altered fungal endophyte community composition, increased the heterogeneity of fungal communities, reduced pathogen abundance, and decreased the diversity of the endophytic fungal community. Inoculation with pathogenic fungi decreased the abundance of bacterial endophytes relative to control and fungicide-treated plants. We then investigated the potential of a common fungal endophyte isolated from this study, Ophiocordyceps sp., as a biological control agent for Helicoverpa zea, a common insect pest in hemp. Contrary to our expectations, larvae preferred food inoculated with Ophiocordyceps sp., although it did not alter the growth or mortality of larvae. Together, our results indicate that hemp-associated endophyte communities are sensitive to abiotic and biotic manipulations and that fungicide application impacts nontarget microorganisms that could confer important functions for crop health. We encourage future studies to analyze the impact of biological control agents on host ecology in an integrated pest management plan and to examine ways to better utilize existing microbial associations to create biological controls. [Figure: see text] Copyright © 2025 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.